Optimization of speed droop governor operation at the gas turbine cogeneration unit - Benriwati Maharmi; Ilham Cholid; Syafii Syafii; Engla Harda Arya (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Variations in customer demand for active power can impact frequency levels, potentially leading to instability within the electrical power system. To uphold system stability, it becomes essential to control the provision of active power to ensure the frequency remains consistent. This research aims to develop a simulation model for optimizing of the operation of the speed droop governor at the gas turbine cogeneration unit. This research used the quantitative method and descriptive statistical analysis techniques. The simulation model was employed as a simulator for operating the speed droop governor for frequency regulation in the electrical system. The gas turbine cogeneration unit 2 operational data of the speed droop values was used to analyze the influence of the generating unit’s response to changes in frequency. The analysis and simulation results revealed the gas turbine cogeneration unit 2 speed droop value of 4%, which was considered ideal for maintaining the stability of the 60 Hz nominal frequency required by customers.